The effect of climate change on crop wild relatives - Jarvis, Andy; Lane, Annie; Hijmans, Robert J. (Elsevier, 2008)
Crop wild relatives are an important source of genetic diversity for crop improvement. However, the survival of some of these wild plant species could be threatened because of climate change. We used current and projected future climate data for ∼2055, and a climate envelope species distribution model to predict the impact of climate change on the wild relatives of peanut (Arachis), potato (Solanum) and cowpea (Vigna). We considered three migrational scenarios for modeling the range shifts (unlimited, limited, and no migration). Climate change strongly affected all taxa, with an estimated 16–22% (depending on migration scenario) of these species predicted to go extinct and most species losing over 50% of their range size. Moreover, for many species, the suitable areas become highly fragmented. Arachis were the most affected group, with 24–31 (depending on the migration scenario) of 51 species projected to go extinct and their distribution area on average reduced by 85–94%, depending on the migration scenario, over the next 50 years. The number of patches was predicted to decrease by 19% under the no migration scenario or increase by 4% assuming unlimited migration. Patch size decreased by 55–60%. For Solanum, 7 (no migration) to 13 (unlimited migration) of 108 species were predicted to go extinct, and their range sizes were reduced by approximately 38–69%. The number of patches was predicted to decrease by 34% (no migration) or increase 7% (unlimited migration) and patch size decreased by 20 (unlimited migration) to 37% (no migration). In terms of species extinction, Vigna was the least affected of the three groups, losing no species (unlimited migration) to 2 species (no migration) of the 48 species in the genus. The mean range size was predicted to decrease by 65% (no migration) or increase 8% (unlimited migration), with 8–41 of the 48 species losing more than 50% of their current geographic range. The number of Vigna patches increased by 12–115%, but the size of those patches shrunk by 51–59%. Our results suggest that there is an urgent need to identify and effectively conserve crop wild relatives that are at risk from climate change. While increased habitat conservation will be important to conserve most species, those that are predicted to undergo strong range size reductions should be a priority for collection and inclusion in genebanks.